Bangladesh : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2011)
Growth performance in Bangladesh is improving, but macroeconomic imbalances have also emerged. Medium-term growth targets are likely to intensify macroeconomic pressures if not managed well. Longer-term growth prospects hinge on generating sufficient resources to relieve infrastructure bottlenecks and ensuring a competitive business environment focused on labor-intensive activities. There is a need to build on the momentum of recent reforms. To ensure a stable macroeconomic environment, vigilance is foremost required on the fiscal front. The focus is on accelerating growth-promoting structural reforms, while ensuring a stable macroeconomic environment.